A review of phytotherapy of Acne vulgaris - Marija Glavas Dodov; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2009)
Acne vulgaris (acne) is a cutaneous pleomorphic disorder of the pilosebaceous unit involving abnormalities in sebum production and is characterized by both inflammatory (papules, pustules and nodules) and non-inflammatory (comedones, open and closed) lesions. Propionibacterium acnes and Staphylococcus epidermidis are common pus-forming microbes responsible for the development of various forms of acne. This disease remains a common condition in industrialized societies, with many mainstream treatment options available. There are many acne products on the market, and making an appropriate selection can be daunting. Common therapies that are used for the treatment of acne include topical, systemic, hormonal, herbal and combination therapy. Topically used agents are benzoyl peroxide, antibiotics and retinoid. Systemically used agents are antibiotics and isotretinoin. However, all such treatments carry risks and none is completely satisfactory. Natural alternatives are gaining greater research support, and have much to offer clinically in this disorder. This review focuses primarily on herbal treatments for acne that show scientific evidence of clinical efficacy, as well as the more common herbs shown to be useful in the treatment of this dermatologic disorder.